2021
DOI: 10.2147/jmdh.s311225
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Physical Inactivity on the Risk of Disability and Hospitalization in Older Patients with Advanced Lung Cancer

Abstract: This prospective observational study aimed to explore the influence of physical inactivity during initial chemotherapy on the risk of disability and hospitalization in later life among older patients with advanced non-small-cell lung cancer (NSCLC). Patients and Methods: Patients aged 70 or above who were scheduled to receive first-line chemotherapy for newly diagnosed advanced NSCLC were recruited for the study. An electronic pedometer was used to measure daily steps; based on the change rate (cutoff: −12.5%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…Particularly in the context of patients with cancer who underwent surgery, early mobilization and physical activity has been shown to be important for decreasing hospital length of stay and, in turn, healthcare costs. 10 , 141 , 207 According to Hall et al, hospital inpatient and hospice stays, community care, outpatient appointments, out-of-hours service, and travel costs were the main costs related to cancer rehabilitation. 70 Evidently, the adoption of wearable devices can address most if not all of these cost drivers.…”
Section: Discussionmentioning
confidence: 99%
“…Particularly in the context of patients with cancer who underwent surgery, early mobilization and physical activity has been shown to be important for decreasing hospital length of stay and, in turn, healthcare costs. 10 , 141 , 207 According to Hall et al, hospital inpatient and hospice stays, community care, outpatient appointments, out-of-hours service, and travel costs were the main costs related to cancer rehabilitation. 70 Evidently, the adoption of wearable devices can address most if not all of these cost drivers.…”
Section: Discussionmentioning
confidence: 99%
“…12 Huang et al 13 reported that the deleterious effect of poor sleep was exacerbated by physical inactivity in the context of all causes and disease-specific mortality with an above tenyear follow-up in a sample of nearly four hundred thousand people. Yonenaga et al 14 also reported that poor physical activity patterns were highly associated with diminished disability and survival among lung cancer patients. Tabaczynski et al 15 reported that even ten minutes of decreased physical inactivity daily leads to increased quality of life among kidney cancer survivors.…”
Section: _ Introductionmentioning
confidence: 98%